Redescription of Alopecosa albostriata (Araneae: Lycosidae) based on specimens from Siberia - Marusik, Yuri M. (Zootaxa, 2018)
Alopecosa albostriata (Grube, 1861), originally described from Western Yakutia, is redescribed based on specimens from Siberia. Although A. albostriata is known to be distributed in Kazakhstan, Russia, China and Korea, with records attributed to more than 30 taxonomic entries, and is considered as a senior synonym of nine species (all described from China), it is actually restricted to Siberia and was illustrated only in two publications. All synonyms and records from China, Kazakhstan and Korea refer to species related to Mustelicosa dimidiata (Thorell, 1875). Among Palaearctic species, A. albostriata is most similar to A. mutabilis (Kulczyński, 1908). Comparative figures are provided for the latter species. These two species, together with A. exasperans (O. Pickard-Cambridge, 1877) form the albostriata species group occurring across Siberia and the northern Nearctic. Male palps in this species group are most similar to those in Mustelicosa Roewer, 1960, and most likely that species group will be transferred to this genus. Distribution records of A. albostriata are shown on map.